The Development of Political Institutions : Power, Legitimacy, Democracy - Ferrara, Federico (Book collections on Project MUSE., 2022)
"While the literature on "new institutionalism" explains the stability of institutional arrangements within countries and the divergence of paths of institutional development between countries, Federico Ferrara improves upon existing explanations of the development of political institutions, taking a "historical institutionalist" approach to theorize dynamic processes of institutional reproduction, institutional decay, and institutional change. With regard to each of these outcomes, Ferrara synthesizes "power-based" or "power-distributional" explanations and "ideas-based" "legitimation explanations." Among his more significant contributions, he specifies the psychological "microfoundations" of processes of institutional development, drawing heavily from the findings of experimental psychology to ensure that the explanation is grounded in clear and realistic assumptions regarding human motivation, cognition, and behavior. Aside from being of interest to scholars and graduate students in political science and other social-scientific disciplines whose research concentrates on the genesis of political institutions, their evolution over time, and/or their impact on the stability of political order and the quality of governance, the book may feature as required reading in graduate courses and seminars in comparative politics where the study of institutions and their development ranks among the subfield's most important subjects"--